A case of near-fatal bronchospasm in a child with severe bronchopulmonary dysplasia during tracheostomy. (January 2020) - Gilley, David R.; Gov-Ari, Eliav
Abstract: Bronchopulmonary dysplasia (BPD) is a condition marked by prolonged ventilator and oxygen requirement due to underlying arrested lung development. Tracheostomy is a staple in long-term establishment of pediatric airways in this condition, and has many benefits. However, these children's airways can be very tenuous. We present a case of a child with severe BPD who developed extreme bronchospasm during tracheostomy. We also briefly review current literature in the management of such children's airways and potential directions for future management.